Development of mongo spread - Penaranda, Sarah G.
Mongo spread was developed from a blend of dehulled mongo, cococream and sugar. Boiling the mongo in water at a mongo to water ratio of 1:8.5 resulted to a product more acceptable than that made from 1:9 and 1:8 mongo to water ratios. Blending the soft cooked mongo in the waring blendor resulted to a homogenous mixture preferred by the panelists. A final viscosity of 24 seconds / funnelful of cooked mixture taken at 70°C resulted to a spreadable product which received a high rating from the panelists. Among the three different formulations used, the mongo spread made from 69.21% mongo, 7.91% cococream and 22.87% sugar was preferred. The developed product was described as described as brownish-yellow in color, homogeneous with the right degree of sweetness and spreadability. Average acceptability rating of the product was 7.4. Heat penetration studies were conducted so as to determine an adequate process based on the heat penetration characteristic of the product and a selected reference organism. Lethality of the process at 250°F for 1 hour was computed to be greater than the lethality of a 5D process using Clostridium thermosaccharolyticum as reference organism.